Innovations, technological specialisation and economic growth in the EU - Jungmittag, Andre; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
The paper analyses the effects of innovations, technological specialisation and technology diffusion on economic growth and convergence of the EU countries from 1969 to 1998. The empirical analysis is based on a panel data model, which enables us, on the one hand, to assess the impacts of these three factors as well as of the usual production factors on long-term economic growth, and, on the other hand, to calculate their partial contributions to β- and σ-convergence of labour productivities within the EU. The results show that besides capital accumulation, transferable technical knowledge is a driving force of growth for catching-up EU countries, while it is the level of Ricardian technological specialisation for advanced EU countries. Furthermore, technology diffusion is a main driving force for the convergence of labour productivities, while different levels of Ricardian technological specialisation slow down convergence. ∗
Economic Papers